Harmonic Suppression Rectangular Patch Antenna with Circularly Polarized - Nurzaimah Zainol; Zahriladha Zakaria; Maisarah Abu; Mawarni Mohamed Yunus (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
The rectangular patch antenna with proximity coupling at 2.45 GHz is designed and printed on FR-4 substrate with dielectric constant 4.3 and loss tangent 0.019. The overall size of proposed antenna gives 36 % reduction of substrate area as compared to conventional designs. The symmetrical arm of inverted U-stub and U-slot embedded on the transmission feed line suppress harmonic signal effectively at second and third order with minimum reflection coefficients of –0.51 dB and -2.28 dB respectively while circularly polarization was obtained by corner truncated and U-slot on the patch element. The return loss is -23.95 dB at fundamental modes with gain 4.61 dB and axial ratio of 1.48 dB.